Assistance in optimizing production and sales for MSME Skippy Cookie "AYU" in Sukodadi Village, Palembang - Isa, Indra Griha Tofik; Mayasari, Riana (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
UMKM becomes the driving force of the community's economy and becomes a contributor to the income of a region. Palembang is an area that has an even distribution of UMKM in each sub-district, one of them is UMKM Kue Skippy "AYU" which is located in Sukodadi. UMKM Skippy Cookie "AYU" was formed in 1992 and produced peanut cookies as a home industry. Skippy Cookie "AYU" has a distinctive taste that is different from similar skippy cookies and can be a potential product for the Sukodadi area. UMKM skippy cookie "AYU" is a pillar of economic activity for the surrounding community. The problems that occur are no legality of the product, the lack of variety of skippy cookie produced, and no good financial management and factory management. So that this activity aims to increase the income and productivity of UMKM partners through the stages of methods assistance for P-IRT Legalization, assistance for skippy cookie product innovation, marketing training, and factory management assistance, and (4) Evaluation. The result of this activity is an increase in partners' income and productivity from 65% to 80%.